Anak Angkat Dalam Pembagian Harta Warisan Menurut Hukum Islam di Dalam Masyarakat Suku Muna - Hakim, Jamil; Latupono, Barzah; Angga, La Ode (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction: Every ethnic group living in Indonesia has different inheritance procedures and laws. The inheritance of each ethnic group is more influenced by the customs of each tribe when they grow and develop. The regional cultural value system is the highest value and the core of regional customs.Purposes of the Research:  To find out the Position of Adopted Children in the Distribution of Inheritance according to Islamic Law.Methods of the Research: The research used is normative juridical which is descriptive analytical. The research approach uses a statutory approach and a conceptual approach. Sources of research data are primary, secondary, tertiary data which is carried out by looking for library materials, namely studies related to PP RI No 54 of 2007 concerning Implementation of Adoption and Compilation of Islamic Law (KHI).Results of the Research: Adopted children in the Muna tribal community, Islamic law according to KHI have the same position as biological children in the customary law system. The position of adopted children in the distribution of inheritance according to Islamic law in the Muna tribal society, adopted children are positioned as biological children if the adoptive parents do not have biological children.